Penggunaan Metode Fuzzy Failure Mode and Effect Analysis Pada Hasil Inspeksi Proteksi Katodik PT PGAS Solution Area Bekasi - Keisha Dinda Syamikha; Mega Cattleya Prameswari Annissaa Islami (Jurnal Serambi Engineering, 2025)
Cathodic protection is used to prevent corrosion in gas pipeline networks, so it is necessary to conduct regular inspections to ensure its effectiveness. This research uses the Fuzzy Failure Mode and Effect Analysis (Fuzzy FMEA) method to analyse the results of cathodic protection inspections on the PT PGAS Solution Area Bekasi gas pipeline network, identify the causes of failures, and determine the control actions that can be taken based on the cause of the failure. Data obtained from cathodic protection inspection activities and expert interviews show that the most common failures are those with low potential values. FRPN calculations using the Fuzzy FMEA method show that environmental factors are critical causes of low potential failures. The main cause is an environment with a soil barrier that is too high, so control measures can be taken by adding additional anodes, lowering the soil barrier or replacing the anode with a larger one. It is hoped that the results will become a recommendation for companies to solve the problem of low potential value disturbances in cathodic protection.